A phase-field study on the peritectic phase transition in Fe-C alloys. (15th June 2017) - Pan, Shiyan; Zhu, Mingfang; Rettenmayr, Markus
Abstract: A quantitative multi-phase-field model, with an anti-trapping current and involving diffusion in the solid, is proposed to simulate the peritectic phase transition in Fe-C alloys. An interface field method with a newly defined step function is adopted to formulate the governing equation of the multi-phase-field variables. The proposed model is applied to simulate the γ -platelet tip growth during the peritectic reaction and the subsequent peritectic transformation ( γ -platelet thickness growth) in large computational domains of the experimental length scale. It is found that the local liquid concentration at the triple junction point L / δ / γ is slightly higher than the liquid concentration in equilibrium with the δ -phase, but lower than the liquid concentration in equilibrium with the γ -phase. This leads to slight melting of the δ -phase in the vicinity of the triple junction, while the γ -platelet growth continues. Higher tip velocities at higher undercoolings produce a steeper carbon concentration gradient along the γ -platelet's thickness direction, and thus yield a higher thickness growth velocity. It is also found that the ratio of tip and thickness growth velocity of the γ -platelets increases at higher undercoolings, leading to decreasing tip radius and platelet thickness. Good agreement between the simulations and the experimental data reported in literature is achieved, demonstrating the quantitative prediction capabilities of the proposed model, and confirming the diffusion control for the peritectic phase transition close to equilibrium conditions. Graphical abstract: Image